The Influence Of Work Flexibility, Self-Efficacy, And Job Satisfaction On Employees Work Engagement PT. XXX - Yohana Sarah Margareth Br Simanjuntak; Prihatin Lumbanraja; Abdul Rahim Matondang (SEAN Institute, 2024)
Employees at PT XXX found several problems, namely indications of a lack of employee work engagement with the company. There is employee rotation/mutation in line with changes in the organizational structure, whether they like it or not, employees have to accept it and there are delays in employee promotions because they have to meet new requirements in accordance with new regulations. This problem is due to changes in organizational culture which means the company is in a period of adaptation. This phenomenon is also supported by the low sense of enthusiasm for work and the low enthusiasm that makes people want to be involved in company activities. The aim of this research is to determine and analyze the influence of flexibility, self-efficacy and job satisfaction on the work engagement of PT XXX employees. The population in this study numbered under 100 people, namely 85 people, so the entire population will be used as a saturated sample. The results of this research are 1) Work flexibility partially has a positive and significant effect on work engagement of PT XXX employees. 2) Self-efficacy partially has a positive and significant effect on work engagement of PT XXX employees. 3) Job satisfaction partially has a positive and significant effect on the work engagement of PT XXX employees. 3) Work flexibility, self-efficacy and job satisfaction simultaneously influence employee work engagement.